2011
DOI: 10.1186/1471-2261-11-69
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of major infections and adverse outcomes among hospitalized. ST-elevation myocardial infarction patients in Florida, 2006

Abstract: BackgroundST-elevation myocardial infarction (STEMI) patients have risk factors and co-morbidities and require procedures predisposing to healthcare acquired infections (HAIs). As few data exist on the extent and consequences of infections among these patients, the prevalence, predictors, and potential complications of major infections among hospitalized STEMI patients at all Florida acute care hospitals during 2006 were analyzed.MethodsSociodemographic characteristics, risk factors, co-morbidities, procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Annually, HAIs affect 5-10% of all inpatients and 25% of ICU patients. A study investigating the prevalence and clinical impact of major infections among 11,879 hospitalized STEMI patients in Florida, during 2006, showed that infections were present in 16% of those patients [27]. The most prevalent HAIs were urinary tract infections, pneumonia, surgical site infections, and bloodstream infections [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Annually, HAIs affect 5-10% of all inpatients and 25% of ICU patients. A study investigating the prevalence and clinical impact of major infections among 11,879 hospitalized STEMI patients in Florida, during 2006, showed that infections were present in 16% of those patients [27]. The most prevalent HAIs were urinary tract infections, pneumonia, surgical site infections, and bloodstream infections [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the prevalence and clinical impact of major infections among 11,879 hospitalized STEMI patients in Florida, during 2006, showed that infections were present in 16% of those patients [27]. The most prevalent HAIs were urinary tract infections, pneumonia, surgical site infections, and bloodstream infections [27]. The risk of infections was increased by comorbidities, AKI, AHF, major surgical procedures, and indwelling catheters, among other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tors decline with age resulting in a weakened immune system and may explain why older patients are more prone to infections and thus have a worse prognosis for PCI (Nash et al 2011;Truffa et al 2012). Patients with T2DM are prone to malnutrition and disordered metabolism of sugar, protein and other important nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case for patients with a Killip class III or higher (Shiraishi et al 2014). The GRACE risk score is a widely used prognostic scale for acute coronary syndrome and it has been shown to be a meaningful prognostic factor for in-hospital mortality in patients with STEMI (Nassar Junior et al 2013). …”
Section: Discussionmentioning
confidence: 99%